Relationship between global and local modulus of elasticity in beams of argentinean Eucalyptus grandis - Piter, Juan Carlos Jesús (2003)
The present paper reports the results of an investigation regarding the relationship between the global and the local Modulus of Elasticity in sawn tirnber of Argentinean Eucalyptus grandis. Por this purpose an empirical research project with 50 beams in structural sizes subjected to bending was carried out. The results obtained according to European standards show the values of both types of Modulus of Elasticiry and the influence of the more important strength and stiffness reducing growth characteristics on their variation, as well as give evidence of rhe effectiveness of the criterion established in the American standard ASTM O 198 ( 1999) for correcting rhe influence of shear on the global Modulus of Elasticity.